The Effectiveness of Development Results of Pro-show Media Based on Solar System Poem and Song on Student Learning Outcomes - Yeni Kurniawanti; Budiyono Saputro; Sakshi Bahuguna (Journal of Innovation in Educational and Cultural Research, 2020)
The purpose of this study was to determine the effectiveness of the results of the development of poem and song-based proshow media on MI Al-Falah Soropadan District of Pringsurat students' learning outcomes in the solar system material. The research method used is quantitative with One-Group Pretest-posttest design. The subjects of the study were sixth graders of MI AL-Falah Soropadan and teachers in Pringsurat District. The research instruments were pretest and posttest of solar material. T-test results obtained t -73.676, p = 0.00 0.05, which means that the poem and song-based proshow media development results are effective on MI Al-Falah Soropadan Pringsurat District students' learning outcomes in solar system material. Poem and song-based proshow media provide solutions for teachers and students in increasing mastery of science subjects.